Measuring the effect of Classroom Condition on Student performance Egypt Case Study - lamiaa Mostafa; asser youssef (Maǧallaẗ Al-Buḥūṯ Al-Mālīyyaẗ wa Al-Tiğāriyyaẗ)
Student performance is an important factor for the graduate career and it affects his future job. Many conditions can affect the student performance in the university such as the classroom, university infrastructure, the curriculum and the relationship between the teachers. This research paper aims to measure the effecting of classroom condition variables represented by noise, air quality, lighting, classroom weather, classroom size, and cleanness. The research model was tested using a questionnaire. A questionnaire was designed for this purpose and it has been distributed on one of the international universities settled in Egypt, a number of 274 students answered this questionnaire. The researchers used the Structured Equation modeling tests to examine the responses. Noise is the most important variable based on the results of the questionnaire. The results demonstrate that noise, classroom weather, classroom size and cleanness are significant in student performance, however air quality and lightning is not significant for the student performance.